Drugs Trafficking Phenomenon in Border District of Jagoi Babang Indonesia-Malaysia West Kalimantan - Nikodemus - Niko (Jurnal Sosiologi Nusantara, 2020)
This paper aim to describe the development of the phenomena of Drugs Trafficking that occurred in Indonesia-Malaysia border region at Jagoi Babang, Bengkayang Region, West Kalimantan Province. Drugs trafficking through the territory of border region is not a new issues. This issue has been very long and seemingly without a settlement rises. This study used a qualitative descriptive approach. Data that is processed in the form of primary data through observation and secondary data from various sources. Based on the facts and the secondary data were analyzed it was found that the border region is still very vulnerable to the growing of drugs trafficking. Poverty being one cause factor towards the border residents participate in the development of this phenomena. The security limitations of the PLB (cross border post) as well as the large number of "jalur tikus" in the border region of Jagoi Babang became a trigger of Drugs Trafficking in the border region.